Clinical and electrocardiographic evaluation of Systemic Arterial Hypertension in elderly in Primary Care in the Municipality of Parnaíba: (Research, Society and Development, 2024)
Introduction: HBP is a chronic disease with high prevalence in Brazil. As it is a frequently asymptomatic condition, it usually develops complications associated with functional or structural changes in target organs and metabolic changes, with an increased risk of cardiovascular events. Methodology: Prevalence study in a probabilistic sample of elderly people with HBP registered at UBS that serve the Parnaíba region, through clinical and electrocardiographic evaluation. It aims to identify specificities of the population residing in the municipality of Parnaíba that may influence the course of HBP and the incidence of complications. Results: There was a predominance of uncontrolled BP among women (55.5%), age group 70 to 79 years (52%), mixed race (63%), incomplete primary education (66.6%), income of 2 salaries minimum (52%) and sedentary lifestyle (81.5%). Discussion: The results can be explained by the socioeconomic and sociocultural factors of the population. Using the ECG as a control indicator, it is inferred that poorly controlled hypertension, male sex, age range between 70 and 79 years, history of smoking, sedentary lifestyle and being overweight are associated with changes in the ECG, with some of these factors being modifiable. Conclusion: The findings suggest a strong association between myocardial changes and uncontrolled BP and between socioeconomic and sociocultural factors with adherence to treatment and control of blood pressure levels.